TINGKAT PENDAPATAN USAHATANI PADI DAN KONTRIBUSINYA TERHADAP PENDAPATAN PETANI - Nur Syamsiyah; Ahmad Thoriq; Pandi Pardian; Tuti Karyani; Kuswarini Kusno (JURNAL AGRIBISNIS TERPADU, 2017)
This research was conducted in Hegarmanah Village, Sumedang Regency. The village of Hegarmanah in 2011 is the village that has the widest rice harvest area compared to other villages which is 242 hectares, in 2014 the rice field becomes 86.82 hectares and will decrease from year to year as a result of land conversion to non agriculture. The purpose of this research is to know the characteristics of rice farming in Hegarmanah Village and to analyze income level and contribution of paddy farm income to earnings structure of farmer. The research method used qualitative method with research case study technique (case study). The design of farming analysis is needed to know the size of farmer acceptance and R / C ratio analysis. The results obtained 81.25 percent of farmers sell some of their products (semi-commercial) and 25 percent of farmers sell farming products, 18.75 percent of farmers do not sell the results of farming. Farmers with the largest sales quantity only reached 42 quintals or about 75 percent of the total production. R / C ratio of farmers greater than 1 means that rice farming is profitable. Rice farm income contribution to total farmer income varies from 12 percent to 100 percent. Some farmers are still dependent on rice farming, additional income derived from livestock and plantation crops, kostan kostan business, processing industry, service and trade.